The Relationship between Fatigue and Sleep Quality in Patients with Congestive Heart Failure (CHF) - Amrina Rosada; Mohammad Arifin Noor; Suyanto Suyanto (International Journal Of Health Science, 2026)
Congestive Heart Failure (CHF) is a chronic cardiovascular condition characterized by the heart’s inability to pump sufficient blood to meet the body’s metabolic demands, leading to various physical and functional disturbances. Among the most frequently reported symptoms in patients with CHF are fatigue and impaired sleep quality, both of which may negatively affect daily functioning and quality of life. This study aimed to examine the relationship between fatigue and sleep quality in patients with Congestive Heart Failure. A quantitative study with a cross-sectional design was conducted at Sultan Agung Islamic Hospital, Semarang, from September to November 2025. A total of 163 patients with CHF were recruited using a sampling technique based on the Isaac and Michael formula. Data were collected using the Fatigue Severity Scale (FSS) to measure fatigue levels and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, supported by medical record data. Statistical analysis was performed using the Chi-Square test. The results showed that most respondents were male (52.8%), aged 56–65 years (25.1%), and had been diagnosed with CHF for approximately two years (33.1%). More than half of the patients experienced high levels of fatigue (54.6%), while the majority reported poor sleep quality (71.2%). The Chi-Square test revealed a statistically significant relationship between fatigue and sleep quality in patients with CHF (p = 0.001; p < 0.05). This study concluded that low and high fatigue affect sleep quality in CHF patients.  The study highlights the importance of comprehensive nursing care that includes early assessment and management of fatigue and sleep disturbances to improve patient well-being and support optimal clinical outcomes.